The Maine woods - Thoreau, Henry David, 1817-1862 (Thoreau, Henry David, 1817-1862. Works. 1971., 2004)
Henry D. Thoreau traveled to the backwoods of Maine in 1846, 1853, and 1857. Originally published in 1864, and published now with a new introduction by Paul Theroux, this volume is a powerful telling of those journeys through a rugged and largely unspoiled land. It presents Thoreau's fullest account of the wilderness. The Maine Woods is classic Thoreau: a personal story of exterior and interior discoveries in a natural setting--all conveyed in taut, masterly prose. Thoreau's evocative renderings of the life of the primitive forest--its mountains, waterways, fauna, flora, and in.